Cs+ extraction from chloride-rich brine solutions using the calixarene crown ether MAXCalix - Sittel, Thomas; Becker, Karolin; Geist, Andreas; Panak, Petra (Solvent extraction and ion exchange, 2024)
We have developed an extraction method for the retrieval of Cs+ from chloridecontaining salt brine solutions. We employ the calixarene crown ether known as MAXCalix as the extractant, which exhibits a remarkable selectivity for Cs+ over Na+, K+, Mg2+ and Ca2+, with separation factors ranging from 100 to 104. The efficiency of the extraction strongly depends on the chloride concentration in the aqueous phase. Notably, when the chloride concentration reaches 4 mol L−1, we achieve a Cs+ distribution ratio of 7.9. Accordingly, the retrieval of Cs+ from the organic phase is achieved when the HCl concentration is maintained at a low level. In multicomponent chloride brine solutions, the distribution ratios for Cs+ are somewhat lower, yet still fall within the range of 4-6. Nevertheless, these ratios remain favorable for separation purposes. Additionally, the distribution ratios of Na+, K+, Mg2+, and Ca2+ offer insights into the coordination chemistry of MAXCalix. Our experimental data indicate a correlation between ionic size and distribution ratio. Cs+ forms the strongest complex, followed by K+ and Na+, while Mg2+ and Ca2+ exhibit minimal extraction, potentially due to interactions with the diluent. These findings may open new approaches for the development of a decontamination strategy tailored to address salts and brine solutions contaminated with Cs-137.